Statistical quality control and electrical conductivity for evaluation of the uniformity of different drip fertigation solutions - Cosmo, Bruno Marcos Nunes [UNESP]; DE ANDRADE, Mauricio Guy; Galeriani, Tatiani Mayara [UNESP]; Hermes, Eliane; Boas, Márcio Antônio Vilas; Gava, GLAUBER JOSÉ DE CASTRO (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2021)
Population growth has led to an intensified search for ways to increase the efficiency of agricultural production, including improvements of irrigation systems. This work aimed to evaluate the uniformity of different drip fertigation techniques, as well as their monitoring using electrical conductivity measurements and statistical quality control charts. For this, an experiment was performed according to a fully randomized design, with six treatments: T1) water (control); T2) Forth Frutas fertilizer; T3) Fortgreen fertilizer; T4) water (control); T5) Bio Bokashi liquid fertilizer; and T6) swine production wastewater. Each treatment consisted of 25 assays (replications). For the assays, 16 collection points were selected for measurements of volume, pH, and electrical conductivity. The data were analyzed using the Christiansen uniformity coefficient, the distribution uniformity coefficient, and the coefficient of variation of the total flow, employing Tukey’s test (5% level), with statistical quality control charts. The results revealed uniformity above 90% for irrigation and fertigation, while statistically better control was obtained for irrigation. It could be concluded that irrigation and fertigation were similar in terms of uniformity, demonstrating the feasibility of using different fertigation solutions, while the control charts enabled efficient monitoring of the uniformity of the systems.
Controle estatístico de qualidade e condutividade elétrica na avaliação da viabilidade do gotejamento com diferentes soluções de fertirrigação
Keywords: Agricultural reuse; Control charts; Operation monitoring